2022
DOI: 10.1093/rheumatology/keac576
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic sclerosis-associated interstitial lung disease in the EUSTAR database: analysis by region

Abstract: Objectives The prevalence and characteristics of systemic sclerosis-associated interstitial lung disease (SSc-ILD) vary between geographical regions worldwide. The objectives of this study were to explore the differences in terms of prevalence, phenotype, treatment, and prognosis in patients with SSc-ILD from predetermined geographical regions in the EUSTAR database. Methods Patients were clustered into seven geographical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…During the last years, special focus was placed on lung disease in SSc patients. Consequently, biomarkers such as anti-U11/U12 antibodies might be useful to identify patients with rapidly progressing ILD [ 1 , 49 ], especially since the classification criteria marker anti-Scl-70, ACA and anti-RNA Pol III do not effectively allow for stratification, albeit still being useful f identify patients at risk for SSc-ILD [ 49 , 50 , 51 ]. Similarly, it must be determined to what extent these antibodies, in conjunction with other risk factors for SSc-ILD, such as the diffuse cutaneous subset or early disease onset, may identify patients that warrant close monitoring or early and aggressive intervention.…”
Section: Implication For New Treatment Strategiesmentioning
confidence: 99%
“…During the last years, special focus was placed on lung disease in SSc patients. Consequently, biomarkers such as anti-U11/U12 antibodies might be useful to identify patients with rapidly progressing ILD [ 1 , 49 ], especially since the classification criteria marker anti-Scl-70, ACA and anti-RNA Pol III do not effectively allow for stratification, albeit still being useful f identify patients at risk for SSc-ILD [ 49 , 50 , 51 ]. Similarly, it must be determined to what extent these antibodies, in conjunction with other risk factors for SSc-ILD, such as the diffuse cutaneous subset or early disease onset, may identify patients that warrant close monitoring or early and aggressive intervention.…”
Section: Implication For New Treatment Strategiesmentioning
confidence: 99%
“…5 The study also found significant differences in the clinical presentation and management of systemic sclerosisinduced interstitial lung disease across seven geographic regions in Europe, highlighting variations in management and the need to standardize evidence-based clinical guidelines. 6 DOI: https://doi.org/10.17925/RMD.2023. 2.1.42 touchREVIEWS in RMD Similarly, disparities are also rooted in the variable incidences and presentation of rheumatic disease in patients of different sexes and genders.…”
Section: Disparities By Biological Factors Race and Regionmentioning
confidence: 99%